Religion, realism and social theory : making sense of society - Mellor, Philip A. (Theory, culture & society (Unnumbered), 2004)
This text challenges those contemporary sociologists who argue that the notion of 'society' is an outmoded basis for sociological analysis and instead revitalizes the idea that sociology is truly 'the study of society'.